Mechanical behavior of new lightweight concrete with fiber and ingredients - Tiam Shirzadi; Fakhredien Ahmadi Danesh Ashtiani (Numerical Methods in Civil Engineering)
Iran is among the earthquake-prone countries in the world. Since infill-wall materials have a brittle behavior, they result in considerable damage under large displacements. Therefore, it seems essential to modify the behavior of infill-wall’s materials. The present article seeks to correct this drawback by using a kind of ductile lightweight concrete (DLC) with a soft behavior. To this end, lightweight concrete was produced from cement, polypropylene, filler, and fine fibers. In order to obtain the modeling and design parameters in buildings, the compressive strength, stress-strain curve, material ductility, Poisson’s ratio, and shear strength of the mortar were evaluated. According to the results, on average, the compressive strength, Poisson’s ratio, and elastic modulus equaled 6 Mpa, 0. 14, and 800 Mpa, respectively. By using machine learning method the stress-strain graph of DLC has been showed and maximum compressive strength and friction angle of the mortar obtained from the designed setup and regression were 0.633 Mpa and 23°, respectively.